E.C. state aids - Hancher, Leigh 1956-; Ottervanger, Tom; Slot, Pieter J. 1944- (Sweet & Maxwell, 1999)
This text has been updated to include all the major developments since the first edition, it includes commentary on specific sectors such as energy and transport. The work includes narrative on issues relating to state aids in the EU.
Keywords: Europäische Gemeinschaften; Europees recht; Mededingingsrecht; Overheidssteun; Subventions - Droit - Pays de l'Union européenne; Europarecht; Recht; Subsidies -- Law and legislation -- European Union countries; Subvention; Finanzierungshilfe; Europäische Union. Mitgliedsstaaten